2017
DOI: 10.1016/j.nano.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficacy of combination heat shock targeted polymer therapeutics with high intensity focused ultrasound

Abstract: Combination of polymer therapeutics and hyperthermia has been shown to enhance accumulation in selectively heated tumor tissue. The additional use of heat shock (HS)-targeting towards tumor tissues can further enhance accumulation and retention, and improve therapeutic outcomes. In this work, high intensity focused ultrasound (HIFU) was used to generate hyperthermia in prostate tumor tissue. Upregulation of the cell surface HS receptor glucose regulated protein 78 kDa (GRP78) was observed after treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The subsequent heat shock response could directly lead to stressful overexpression of heat shock proteins (HSPs) including HSP110, HSP90, and HSP70 . Due to the obvious contribution to tumor survival and growth of HSPs, some HSP inhibitors were developed to cut down the thermoresistance and improve the curative effect . The Hsp90 inhibitors, 17‐allylamino‐17‐demethoxygeldanamycin (17AAG), can specifically bind to the HSP90 ATP pocket reversibly, thus destroying its thermal‐protected function potently and further leading to the death of cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent heat shock response could directly lead to stressful overexpression of heat shock proteins (HSPs) including HSP110, HSP90, and HSP70 . Due to the obvious contribution to tumor survival and growth of HSPs, some HSP inhibitors were developed to cut down the thermoresistance and improve the curative effect . The Hsp90 inhibitors, 17‐allylamino‐17‐demethoxygeldanamycin (17AAG), can specifically bind to the HSP90 ATP pocket reversibly, thus destroying its thermal‐protected function potently and further leading to the death of cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…Chiang compared radical prostatectomy, high‐dose brachytherapy, cryoablation, and HIFU for localized prostate carcinoma and concluded that whereas oncologic outcomes were similar, the HIFU group had better urinary function, better sexual function, and an improved quality of life. High‐intensity focused US–induced hyperthermia has also been investigated in preclinical studies to trigger the release of chemotherapeutic drugs from temperature‐sensitive liposomes . In general, various forms of focal therapy are all very similar in efficacy.…”
Section: Combined Therapymentioning
confidence: 99%
“…Greater cell uptake and binding of HSP‐targeted polymer after hyperthermia induction was found . Also, in vivo studies showed that the hyperthermia induced GRP78 expression in a prostate xenograft model measured by immunohistochemical analysis was found to be high at 8 h . Therefore, we can use one of these approaches for hyperthermia induction in conjunction with the use of the present copolymer conjugate for future in vivo studies.…”
mentioning
confidence: 94%
“…Previous studies have shown that biocompatible macromolecules like HPMA‐based carrier systems are able to extend blood circulation time and increase accumulation in solid tumors tissue by the EPR effect . Furthermore, we have previously demonstrated that HIFU and plasmonic photothermal therapy (PPTT) generate mild hyperthermia that can enhance heat shock protein expression in cells and accumulation of polymer‐drug conjugates in a tumor model . For example, in previous reports, higher expression of GRP78 through hyperthermia in human prostate cancer cells was measured using flow cytometry.…”
mentioning
confidence: 98%
See 1 more Smart Citation